Femtosecond‐Laser Direct Writing of Metallic Micro/Nanostructures: From Fabrication Strategies to Future Applications. Issue 7 (7th May 2018) - Ma, Zhuo‐Chen; Zhang, Yong‐Lai; Han, Bing; Chen, Qi‐Dai; Sun, Hong‐Bo
Abstract: The past decade has seen growing research interest in developing novel fabrication methodologies for metallic micro/nanostructures toward the rational design and integration of 0D to 3D metallic configurations. Among the various fabrication techniques, femtosecond‐laser direct writing has emerged as a prominent approach to reach this goal and greatly facilitates the development of metallic micro/nanostructure‐enabled applications. Here, a series of femtosecond‐laser‐mediated fabrication strategies, including the two‐photon reduction of metal ions, template‐assisted metal coating and metal filling, photodynamic assembly of metal nanoparticles, and selective nanoparticle sintering, are summarized. Additionally, abundant applications in microelectronics, metamaterials, near‐field optics, microfluidics, micromechanics, and microsensors are introduced in detail. Current challenges and future perspectives in this field are also discussed. Abstract : Recent advances in the femtosecond‐laser direct writing of metallic micro/nanostructures are highlighted. Fabrication strategies, including the two‐photon reduction of metal ions, template‐assisted metal coating and filling, photodynamic assembly of metal nanoparticles, and laser sintering, and their applications in microelectronics, metamaterials, nearfield optics, microfluidics, micromechanics, and microsensors are summarized. Current challenges and future perspectives in this field are also discussed.